Challenges in legitimizing further measures against smoking in jurisdictions with robust infrastructure for tobacco control: how far can the authorities allow themselves to go? - Karl Erik Lund; Gunnar Saebo (BMC, 2024)
Abstract Background According to a recently published study, approximately half of those who currently smoke in Norway have little or no desire to quit despite a hostile regulatory and socio-cultural climate for smoking. On this background, we discuss some challenges that regulators will face in a further tightening of structural measures to curb smoking. Main body Central to our discussion is the research literature concerned with the concept of state-paternalism in tobacco control-the line between an ethically justified interference with the freedom of those who smoke and an exaggerated infringement disproportionate to the same people's right to live as they choose. In countries with an already advanced infrastructure for tobacco control, this dilemma might become quite intrusive for regulators. We ask that if people, who smoke are aware of and have accepted the risks, are willing to pay the price, smoke exclusively in designated areas, and make decisions uninfluenced by persuasive messages from manufacturers-is a further tightening of anti-smoking measures still legitimate? Strengthening of the infrastructure for tobacco control can be seen as a "help" to people who-due to some sort of "decision failure"-continue to smoke against their own will. However, for those who want to continue smoking for reasons that for them appear rational, such measures may appear unwanted, punitive, and coercive. Is it within the rights of regulators to ignore peoples' self-determination for the sake of their own good? We problematize the "help" argument and discuss the authorities' right to elevate the zero-vision of smoking as universally applicable while at the same time setting up barriers to switching to alternative nicotine products with reduced risk. Conclusion We recommend that a further intensification of smoking control in countries that already have a well-developed policy in this area requires that regulators start to exploit the opportunity that lies in the ongoing diversification of the recreational nicotine market.